A Study on Enhancing Government Efficiency and Public Trust: The Transformative Role of Artificial Intelligence and Large Language Models - Hao Qin; Zhi Li (International Journal of Engineering and Management Research, 2024)
This paper examines the transformative potential of Artificial Intelligence (AI), specifically Large Language Models (LLMs), in enhancing government efficiency and public sector service delivery. By integrating AI into various governmental functions such as automated administrative tasks, public safety, resource management, citizen services, policy development, and fraud detection, governments worldwide can significantly streamline operations, improve decision-making, and enhance citizen engagement. Detailed potential case studies from the United States’ IRS and local government agencies like SSA illustrate the successful implementation of AI, demonstrating its substantial benefits in operational efficiency and public satisfaction. The study concludes with strategic recommendations for further AI adoption, emphasizing the importance of robust governance, continuous technological investment, workforce training, and maintaining public trust. This research underscores AI's critical role in modernizing government functions and fostering a more responsive and inclusive public service landscape.